Reforming a complicated income tax system: The political economics perspective - Salvatore Barbaro; Jens Südekum (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2004)
In this paper we analyze the political economics of different strategies to implement revenue neutral reforms of a complicated income tax system ('tax-cut-cum-base-broadening'). We set up a straightforward social choice model where individuals initially have two deduction possibilities from the tax base. The government wants to cut back the tax base exemptions and it can do so symmetrically or asymmetrically. Asymmetrical approaches face the difficulty that even such individuals can vote against an isolated cut (or an abolishment) of a single tax concession who benefit below average from it. In some constellations a symmetrical cut is in fact the only politically feasible option, whereas all asymmetrical reforms would not be supported by the public.
Keywords: 330; Einkommensteuer; Steuerreform; Public Choice; Theorie